Comportamiento y biomasa de tres especies de Stizolobium spp. (Mucuna) como cobertura en suelos ácidos - Alto Mayo San Martín. - Rojas Villalobos, Percy (2004)
The present titled thesis "Behavior and biomass of three species of Stizolobium spp. (Mucuna) as covering in sour floors-High May San Martin". he/she has as objectives: to Determine the behavior of the black mucunas, ash and colored (Stízolobium aterrimun, Stizolobium pruriens and Stizolobium sp.) as covering in sour floors; to Quantify the air bíomass of the three suitable species and to Determine the production costs for each species in study. The experiment was developed in the sector Shimbillo, located in the Km 1,5 Highway Moyobamba to the Center Populated smaller New Progress, located in the District and County of Moyobamba, Region San Martin, valley of the High May; Property of Mr. Alberto Toasts Fences. In the execution the Design of Blocks was used Totally at random (DBCA), with 3 treatments T1 (Mucuna quarter note), T2 (Mucuna ash) and T3 8(colored Mucuna) and 3 repetitions. The results demonstrated that the biggest quantity in floral clusters (11,29), size of flowers (5,83). size of sheaths (11, 77) and seed weight (2 653, 73 Kg/ha), it was obtained with Mucuna ash (Stizolobium pruriens), comparatively with the other species. Mucuna ash (stizolobium pruriens) helshe obtained bigger fresh biomass (25 343,30 Kg/ha) and consequently bigger dry biomass (7 842,30 Kg/ha), in comparison with the other mucuna species.